Orbital Transfers in a Binary Asteroid System Considering Flattening of the Bodies and Solar Radiation Pressure - Santos, L. B.T.; Razoumny, V. Y.; Gomes, V. M. [UNESP]; Prado, A. F.B.A. (MDPI, 2024)
This paper aims to investigate the effects of asteroid size and shape and solar radiation pressure in the trajectories of a spacecraft in transfers between the collinear equilibrium points of a binary non-spherical asteroid system. As an example, we consider the physical and orbital characteristics of the asteroid system 2001SN263. The goal is not to study this system in detail, but to use its parameters to search for transfers considering elongated bodies for the asteroids and compare the results with the solutions obtained when modeling the bodies as point masses. For the propulsion system, bi-impulsive transfers were investigated. In a system composed of asteroids, it is important to take into account the elongation of the asteroids, particularly the body with the most irregular shape, as this has been shown to change the optimal transfer trajectories. By incorporating solar radiation pressure and the size of the bodies into the dynamics, solutions with both lower and higher fuel consumption can be identified. Although the irregular shape and radiation pressure were not used as controls, their effects on the transfers are analyzed. For a system of small bodies, such as an asteroid system, it is very important to consider these perturbations to ensure that the spacecraft will reach the desired point.
Keywords: asteroids; astrodynamics; orbital perturbations; orbital transfers